Diagnostic yield of non-invasive imaging in patients following non-traumatic out-of-hospital sudden cardiac arrest: A systematic review. (February 2019) - Petek, Bradley J.; Erley, Christopher L.; Kudenchuk, Peter J.; Carlbom, David; Strote, Jared; Gatewood, Medley O.; Shuman, William P.; Hira, Ravi S.; Gunn, Martin L.; Maynard, Charles; Branch, Kelley R.
Abstract: Aim: To review data for non-invasive imaging in the diagnosis of non-traumatic out-of-hospital cardiac arrest (OHCA). Data sources: We searched MEDLINE, EMBASE, Cochrane library, and clinicaltrials.gov databases from inception to January 2017 for studies utilizing non-invasive imaging to identify potential causes of OHCA [computed tomography (CT), ultrasound including echocardiography, and magnetic resonance (MRI)]. Study selection: Inclusion criteria were the following: (1) randomized control trials, cohort studies or observational studies; (2) contained a population ≥18 years old with non-traumatic OHCA who underwent diagnostic imaging with CT, MRI, echocardiography, or abdominal ultrasound; (3) imaging was obtained for diagnostic purposes; (4) patients were alive or were undergoing cardiopulmonary resuscitation at the time of imaging; (5) contained potential causes of OHCA. Endpoints studied were the number of potential OHCA causes identified, diagnostic accuracy measures (sensitivity, specificity, positive and negative predictive values), and diagnostic utility (number of imaging findings with reported changes in clinical management). Results: Of the total 5722 studies identified, 17 (0.3%) met inclusion criteria. The majority of studies assessed the utility of CT in OHCA (n = 10), and potential causes of OHCA were found in 8–54% of patients following head, abdominal and/or chest CT. Only 1/17 (6%) studies reported diagnostic accuracy measures, and 9/17 (53%) studies included a time to imaging criteria within 24 h. Conclusion: Although non-invasive imaging is commonly performed in patients after OHCA, its diagnostic utility remains poorly characterized. Prospective studies are needed for appropriate imaging selection and their potential impact on treatment and outcome.